Teaching Entrepreneurship by Using the â€œStudent Enterprise Modelâ€ to Future Vocational Teachers - GothUrsula SmÃ¥land; SchÃ¶nEldbjÃ¸rg Marie (Journal of Education and Vocational Research, 2015)
A recent focus worldwide is on education to foster entrepreneurship, mostly at the college level. Norway’s Knowledge Promotion Reform introduces entrepreneurial thinking already in upper-secondary education and gives to vocational teachers the task of preparing students in these areas. The Oslo and Akershus University College, Institute for Vocational Education, teaches entrepreneurship both on theoretical and practical level to students preparing to teach in public schools. This article examines the practical dissemination of entrepreneurship through the project â€œStudent Enterprise,â€ and examines how the targets of this module â€“ those in training to be vocational teachers â€“ perceived its relevance. The research question was pursued through a strategic literature search, a quantitative analysis of teaching assessments from 114 students (course evaluations), and a survey of 18 vocational teachers-in-training. The literature search and theories of Dreyfus & Dreyfus and Schumpeter formed the basis for analysis and discussion. The "Student Enterprises" teaching plan and method aims to promote entrepreneurial thinking and convey direct experience to future vocational teachers, who will in turn impart these lessons to their students, with the implication that they will use the same model with their students. The results show that today’s praxis is not effective with all vocational-teaching students as a method of preparing teachers to teach entrepreneurial skills. Authors found a high level of dissatisfaction among future vocational teachers with the Student Enterprises module, but the specifics of the dissatisfaction could not be clearly ascertained, suggesting a need for further assessment to better adapt this entrepreneurial pedagogy to students’ needs.